PENGARUH PENGGUNAAN MEDIA LIVEWORKSHEET DAN MOTIVASI TERHADAP HASIL BELAJAR SISWA PADA MATERI GAYA GRAVITASI KELAS 4 SEKOLAH DASAR - Malika Novanda Alfitria; Sudi Dul Aji; Arnelia Dwi Yasa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low learning outcomes of elementary school students on the topic of gravitational force indicate the need for innovative learning media to improve students' motivation and academic performance. This study aims to examine the effect of using liveworksheet media and learning motivation on students' learning outcomes in grade 4 of elementary school. The research employed a quantitative method with a quasi-experimental design. The sample consisted of 27 students in the experimental class and 27 students in the control class. The instruments used were learning outcome tests and learning motivation questionnaires. The pretest t-test showed no significant difference between the two classes (Sig. = 0.293). The posttest t-test revealed a significant difference in learning outcomes (Sig. = 0.006). The t-test for learning motivation also showed a significant difference between the classes (Sig. = 0.000). The f-test (ANOVA) indicated a significant interaction between the use of Liveworksheet media and learning motivation on students' learning outcomes (Sig. = 0.021). These findings demonstrate that the use of Liveworksheet media and learning motivation have a positive influence on improving students' learning outcomes.